Characterization of the 5′ Ends for Polyadenylated RNAs Synthesized during the Replication of Hepatitis Delta Virus - Gudima, Severin (American Society for Microbiology, 1999)
The genome of hepatitis delta virus (HDV) is a 1,679-nucleotide (nt) single-stranded circular RNA that is predicted to fold into an unbranched rodlike structure. During replication, two complementary RNAs are also detected: an exact complement, referred to as the antigenome, and an 800-nt polyadenylated RNA that could act as the mRNA for the delta antigen. We used a 5′ rapid amplification of cDNA ends procedure, followed by cloning and sequencing, to determine the 5′ ends of the polyadenylated RNAs produced during HDV genome replication following initiation under different experimental conditions. The analyzed RNAs were from the liver of an infected woodchuck and from a liver cell line at 6 days after transfection with either an HDV cDNA or ribonucleoprotein (RNP) complexes assembled in vitro with HDV genomic RNA and purified recombinant small delta protein. In all three situations the 5′ ends mapped specifically to nt 1630. In relationship to what is called the top end of the unbranched rodlike structure predicted for the genomic RNA template, this site is located 10 nt from the top, and in the middle of a 3-nt external bulge. Following transfection with RNP, such specific 5′ ends could be detected as early as 24 h. We next constructed a series of mutants of this predicted bulge region and of an adjacent 6-bp stem and the top 5-nt loop. Some of these mutations decreased the ability of the genome to undergo antigenomic RNA synthesis and accumulation and/or altered the location of the detected 5′ ends. The observed end located at nt 1630, and most of the novel 5′ ends, were consistent with transcription initiation events that preferentially used a purine. The present studies do not prove that the detected 5′ ends correspond to initiation sites and do not establish the hypothesis that there is a promoter element in the vicinity, but they do show that the location of the observed 5′ ends could be controlled by nucleotide sequences at and around nt 1630.